A new species of African Mole-rat (Fukomys, Bathyergidae, Rodentia) from the Zaire-Zambezi Watershed - van Daele, Paul A.a.g.; Blondé, Pieter; Stjernstedt, Robert; Adriaens, Dominique (Zootaxa, 2013)
A new species of bathyergid mole-rat, Fukomys vandewoestijneae, is described from an area on the Zaïre-Zambezi wa-tershed, centred on the Ikelenge pedicle in the North-Western province of Zambia. It is diagnosed by a unique combination of morphological (size, lack of clear headmarks), chromosomal (2n= 44) and DNA sequence characteristics. This medi-um-sized species belongs to the Giant mole-rat “F. mechowii” clade, which was hitherto considered monotypic. Its known distribution is limited to the Ikelenge pedicle of Zambia and adjacent areas in the Democratic Republic of Congo (DRC) and presumably Angola. Colonies of this social mole-rat were observed in the chanas (dambos), degraded miombo wood-land and in villages. Although presumably sympatric in historical times with F. mechowii, no overlap in the species current distribution could be established. This local endemic species adds further evidence to the conservation importance of the two-pedicle region (Ikelenge pedicle (Zambia)